Socialisation professionnelle en ligne : étude cyber-ethnographique d’une communauté virtuelle de maîtres supplémentaires - Quentin Magogeat (Éducation et Socialisation)
Based on a netnographic study of a virtual community of additional teachers in primary school constituted on social networks, we sought to identify and understand the uses of this technological tool favoring remote and asynchronous communication. The analysis of the discussions between the additional teachers on the virtual group made it possible to capture at least three uses. First, the Facebook group is a space of professional socialization between peers, to grow to a common culture of additional teachers. Secondly, the members seem to use this group as a space of exchange and circulation of knowledge, favoring their participation and their enrolment in the plan "Plus de maîtres que de classes". Finally, the analysis of the discussions makes it possible to identify this group as an emotional and social support space, through which some additional teachers take advantage of it to share professional difficulties related to the exercise of their function